2020
DOI: 10.1111/1750-3841.15537
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nanoemulsion particle size on the bioavailability and bioactivity of perilla oil in rats

Abstract: The aim of this study was to investigate the bioavailability and bioactivity of perilla (Perilla frutescens) oil nanoemulsions prepared at different homogenization pressures by measuring the weight, fatty acid profile, and antioxidant and anti‐inflammatory properties in rats. The high‐pressure homogenization significantly reduced the particle size of perilla oil nanoemulsions and enhanced their stability, and the minimum particle size was 293.87 ± 6.55 nm at 120 MPa. There was an increase in the weight and fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 43 publications
0
15
0
1
Order By: Relevance
“…Nanoemulsions are colloidal dispersions of two immiscible liquids stabilized by surfactants with small droplet sizes [ 16 , 17 ]. The advantages of this system include the enhancement of the solubility and bioavailability of lipophilic molecules (e.g., CV), controlled drug release, and protection from enzymatic degradation [ 18 , 19 ]. Nanoemulsions can be produced using different methodologies, including high-energy methods such as high-pressure homogenization, ultrasonication, and microfluidization [ 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nanoemulsions are colloidal dispersions of two immiscible liquids stabilized by surfactants with small droplet sizes [ 16 , 17 ]. The advantages of this system include the enhancement of the solubility and bioavailability of lipophilic molecules (e.g., CV), controlled drug release, and protection from enzymatic degradation [ 18 , 19 ]. Nanoemulsions can be produced using different methodologies, including high-energy methods such as high-pressure homogenization, ultrasonication, and microfluidization [ 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the administration of 5 g kg −1 perilla oil for 21 days increased ALA and EPA levels in the liver. 64 In contrast, Rincón-Cervera et al 63 reported an increase in DHA levels after supplementing with rosa mosqueta, chia, and sacha inchi oils. This difference could be attributed to the higher ALA content in BSO or the different LA : ALA ratios.…”
Section: Food and Function Papermentioning
confidence: 94%
“…SP-NEs were prepared employing the method of homogenization [ 21 , 24 ] using the JN-02HC high-pressure homogenizer (Juneng Biotechnology Co., Ltd., Guangzhou, China). We started with the selection of components for phase A and phase B, and the chosen criteria were whether the sample was clarified or stratified.…”
Section: Methodsmentioning
confidence: 99%